Cooling Aluminium Coils by Outdoor Air - Sedlacek, Dieter; Hausnerova, Berenika (Manufacturing Technology Journal, 2019)
Aluminium extraction and production is energy intensive and have a relatively large environmental impact. One of the steps in the production of sheet aluminium is the cooling of the rolled metal after the hot mill. This study introduces an option to replace the active cooling by an environmental friendly method and eliminate the otherwise necessary logistic step of relocating the coils after cooling. This was done by developing a thermal model of the coils, calculating, based on the model, the required airflow and verifying it with test series. The experimental setup is in a high-bay storage facility belonging to a aluminium production line. The results of the test series show the differences between simulations and real life settings.
Keywords: Energy efficiency; Cooling coils; High-bay storage; Outdoor air; Energy savings